P105 Therapists acceptability of delivering a psychologically informed gait rehabilitation intervention in early rheumatoid arthritis (GREAT): a qualitative interview study. (20th April 2020) - Sekhon, Mandeep; Godfrey, Emma; Hendry, Gordon; Foster, Nadine E; Hider, Samantha; van der Leeden, Marike; Mason, Helen; McConnachie, Alex; McInnes, Iain; Patience, Aimie; Sackley, Catherine; Steultjens, Martin; et al.
Abstract: Background: Great Strides is a brief psychologically informed gait rehabilitation intervention (two compulsory face-to-face sessions and up to four optional sessions delivered over 3 months) aimed at improving lower limb function for adults with early rheumatoid arthritis (RA). As part of the Gait Rehabilitation in Early Arthritis Trial (GREAT) feasibility study, physiotherapists and podiatrists received two days of bespoke training delivered by psychologists, physiotherapists and podiatrists on i) the gait rehabilitation exercise programme (six walking exercises) ii) aspects of motivational interviewing (MI) and iii) delivery of key behaviour change techniques (BCTs) to facilitate motivation and adherence to the Great Strides intervention. The training was supported by a bespoke therapist manual and session checklists. The aim of this study was to explore therapists' acceptability of: (1) the bespoke training received and (2) delivering the intervention within the GREAT feasibility study. Methods: All 10 therapists who received training were invited to complete semi-structured interviews. The topic guide was informed by the Theoretical Framework of Acceptability (TFA). Interviews were audio recorded, professionally transcribed and a deductive thematic analysis was applied. Data were coded into six TFA constructs (Affective Attitude; Burden; Intervention Coherence; Opportunity Costs; Perceived Effectiveness; Self-efficacy). Results: Nine out of ten therapists (four physiotherapists, five podiatrists) participated in the semi-structured interviews. Five therapists (four physiotherapists, one podiatrist) delivered the Great Strides intervention. Key barriers and enablers with regards to the acceptability of the bespoke training and intervention delivery were identified. Training: Therapists liked the supportive training environment (affective attitude), understood the purpose of the training sessions (intervention coherence), reported that the role play exercises aided their confidence in applying MI and BCTs (self-efficacy) and found that the training sessions were vital preparation for delivering the intervention (perceived effectiveness). Aspects of training which were considered unacceptable included the lack of time to attend the training sessions (opportunity costs). Delivery: All therapists enjoyed applying MI and BCTs to encourage participants to complete the gait exercises (affective attitude) and valued the opportunity to provide individualised care (intervention coherence). Barriers associated with acceptability included the use of trial-related materials (e.g. checklist) during intervention delivery (burden), interference of intervention delivery with routine clinical workload (opportunity costs) and the time delay between receiving training and initial intervention delivery (perceived effectiveness). Conclusion: Both GREAT intervention training and delivery were considered acceptable to most therapists. The results have guided key refinements for training and intervention delivery for the GREAT internal pilot and full trial (e.g. remote access to training, timing of training in relation to intervention delivery). These refinements have the potential to improve the bespoke training and enhance the delivery of the Great Strides intervention maximising efficiency and potential for effectiveness. Disclosures: M. Sekhon None. E. Godfrey None. G. Hendry None. N.E. Foster None. S. Hider None. M. van der Leeden None. H. Mason None. A. McConnachie None. I. McInnes None. A. Patience None. C. Sackley None. M. Steultjens None. A. Williams None. J. Woodburn None. L. Bearne None.